The Effect of Operating Cash Flow, Liquidity, and Leverage on Financial Distress in Manufacturing Companies - Marcia Audrey Baskoro; Yovita Ariani (Jurnal Penelitian Ekonomi dan Akuntansi JPENSI, 2026)
This study aims to obtain empirical evidence and analyze the partial and simultaneous effects of operating cash flow, liquidity proxied by the current ratio, and leverage proxied by the debt to asset ratio on financial distress. The population consists of manufacturing companies in the Basic Materials, Consumer Cyclicals, and Consumer Non-Cyclicals sectors listed on the Indonesia Stock Exchange in 2024. The sample was selected using purposive sampling and comprised thirty one companies. Multiple regression analysis was employed using EViews thirteen. The results show that operating cash flow, liquidity, and leverage simultaneously affect financial distress. Partially, operating cash flow and liquidity have positive effects on financial distress, whereas leverage has a negative effect on financial distress during the observed research period